Downtown curbside parking capacity - Richard J. Arnott; Eren Inci; John Rowse (Center for Economic Studies and ifo Institute (CESifo), 2013)
In downtown areas, what proportion of curbside should be allocated to parking? In contrast to most previous work on the economics of parking, this paper focuses on optimal curbside parking capacity in both first-best (where pricing is efficient) and second-best (where pricing is inefficient) environments. It first considers the situation where there is only curbside parking, and then the situation where there may be both curbside and private garage parking. For each situation, it examines the short run in which curbside parking capacity is fixed and the long run in which it is a policy variable.
Keywords: D04; L91; R41; R48; 330; cruising for parking; curbside parking; curbside parking capacity; garage parking; traffic congestion; Ruhender Verkehr; Stadtzentrum; Kapazitätsauslastung; Verkehrsstau; Verkehrsaufkommen; Theorie